Facebook Automatic Translation: Ketidakkonsistensian Penyampaian Arti Bahasa bagi Penggunanya - Luh Eka Susanti; Kadek Ayu Ekasani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to identify the form of inconsistency in the translation results of Facebook Automatic Translation and to find out the translation procedure that should be processed by Facebook Automatic Translation. The method used is an indirect observation by observing the uploads of Facebook users, which means it feels awkward. The technique of collecting data in this study used simple random sampling. The study results indicate that there are deviations from the results of the translation carried out by Facebook, thus triggering misperceptions that can be a problem for readers. In conclusion, the inconsistency in conveying the Source Language (SL) meaning to the Target Language (TL) is caused by the absence of equivalent words, especially the source language originating from Balinese. Keywords: Facebook Automatic Translation, Translation Features, Translation Procedure